Real time localisation of mobile robots using odometer and an external sensor in smart factory - Chan, Kai Wen (Nanyang Technological University, 2020)
In this study, we aim to introduce a method to solve the problem of localizing AGVs in an indoor environment. This problem exists in the real world as it is still not possible to acquire noise free measurements from an ordinary IMU sensor. This project is aimed at integrating the IMU and odometry readings in order to obtain a more accurate position of the AGV in a particular location. Also, this project is aimed at finding a cost effective method of achieving autonomous navigation of a robot without the use of expensive equipment like the LiDAR. The proposed method is to retrieve odometry readings from the AGV encoders and thereafter create a fusion algorithm with the IMU to obtain an accurate position of the AGV. Additionally, ultrasonic sensors will be used by the AGV for collision avoidance.